Perceptions of Indonesian Teachers on Integrating Digital Technologies into Teaching Activities - Harsabawa, Jalu; Ernawati, Asih (Smart Edu Center, 2023)
Digital literacy is crucial in many aspects, especially since that most activities are facilitated by digital tools. Education is another profession in which digital literacy is vital. As time passes, teachers will be required to use digital technologies into their teaching and learning activities. The pandemic was also one of the reasons teachers were pushed to integrate teaching since teaching and learning cannot be done in the classroom. Although there are some teachers who integrated the teaching prior to the epidemic. According to the findings of this study, teachers are